Environmental heterogeneity, bird-mediated directed dispersal, and oak woodland dynamics in Mediterranean Spain - Purves, Drew W.; Zavala, Miguel A.; Ogle, Kiona; Prieto, Fernando; Benayas, Jose M. Rey (ECOLOGICAL MONOGRAPHS, 2007)
Vegetation dynamics in complex landscapes depend on interactions among environmental heterogeneity, disturbance, habitat fragmentation, and seed dispersal processes. We explore how these features combine to affect the regional abundances and distributions of three Quercus (oak) species in central Spain: Q. faginea (deciduous tree), Q. ilex (evergreen tree), and Q. coccifera (evergreen shrub). We develop and parameterize a stochastic patch occupancy model (SPOM) that, unlike previous SPOMs, includes environmentally driven variation in disturbance and establishment. Dispersal in the model is directed toward local (nearby) suitable habitat patches, following the observed seed-caching behavior of the European Jay. Model parameters were estimated using Bayesian methods and survey data from 12 047 plots. Model simulations were conducted to explore the importance of different dispersal modes (local directed, global directed, local random, global random). The SPOM with local directed dispersal gave a much better fit to the data and reproduced observed regional abundance, abundance-environment correlations, and spatial autocorrelation in abundance for all three species. Model simulations suggest that jay-mediated directed dispersal increases regional abundance and alters species-environment correlations. Local dispersal is estimated to reduce regional abundances, amplify species-environment correlations, and amplify spatial autocorrelation. Parameter estimates and model simulations reveal important species-specific differences in sensitivity to environmental perturbations and dispersal mode. The dominant species Q. ilex is estimated to be highly fecund, but on the edge of its climatic tolerance. Therefore Q. ilex gains little from directed dispersal, suffers little from local dispersal, and is relatively insensitive to changes in habitat cover or disturbance rate; but Q. ilex is highly sensitive to altered drought length. In contrast, the rarest species, Q. coccifera, is well adapted to the climate and soils but has low fecundity; thus, it is highly sensitive to changes in dispersal, habitat cover, and disturbance but insensitive to altered drought length. Finally, Q. faginea is estimated to be both at the edge of its climatic tolerance and to have low fecundity, making it sensitive to all perturbations. Apparently, co-occurring species can exhibit very different interactions among dispersal, environmental characteristics, and physiological tolerances, calling for increased attention to species-specific dynamics in determining regional vegetation responses to anthropogenic perturbations.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: biogeography; climate change; climate envelope; corvids; dispersal limitation; Garrulus; Holm oak; Iberian peninsular; incidence function; patch model; species migration; zoochory

Environmental heterogeneity, bird-mediated directed dispersal, and oak woodland dynamics in Mediterranean Spain - Purves, Drew W; Zavala, MIGUEL a; Ogle, Kiona; Prieto, Fernando; Benayas, Jose M Rey (ECOLOGICAL MONOGRAPHS, 2007)
Vegetation dynamics in complex landscapes depend on interactions among environmental heterogeneity, disturbance, habitat fragmentation, and seed dispersal processes. We explore how these features combine to affect the regional abundances and distributions of three Quercus (oak) species in central Spain: Q. faginea (deciduous tree), Q. ilex (evergreen tree), and Q. coccifera (evergreen shrub). We develop and parameterize a stochastic patch occupancy model (SPOM) that, unlike previous SPOMs, includes environmentally driven variation in disturbance and establishment. Dispersal in the model is directed toward local (nearby) suitable habitat patches, following the observed seed-caching behavior of the European Jay. Model parameters were estimated using Bayesian methods and survey data from 12 047 plots. Model simulations were conducted to explore the importance of different dispersal modes (local directed, global directed, local random, global random). The SPOM with local directed dispersal gave a much better fit to the data and reproduced observed regional abundance, abundance-environment correlations, and spatial autocorrelation in abundance for all three species. Model simulations suggest that jay-mediated directed dispersal increases regional abundance and alters species-environment correlations. Local dispersal is estimated to reduce regional abundances, amplify species-environment correlations, and amplify spatial autocorrelation. Parameter estimates and model simulations reveal important species-specific differences in sensitivity to environmental perturbations and dispersal mode. The dominant species Q. ilex is estimated to be highly fecund, but on the edge of its climatic tolerance. Therefore Q. ilex gains little from directed dispersal, suffers little from local dispersal, and is relatively insensitive to changes in habitat cover or disturbance rate; but Q. ilex is highly sensitive to altered drought length. In contrast, the rarest species, Q. coccifera, is well adapted to the climate and soils but has low fecundity; thus, it is highly sensitive to changes in dispersal, habitat cover, and disturbance but insensitive to altered drought length. Finally, Q. faginea is estimated to be both at the edge of its climatic tolerance and to have low fecundity, making it sensitive to all perturbations. Apparently, co-occurring species can exhibit very different interactions among dispersal, environmental characteristics, and physiological tolerances, calling for increased attention to species-specific dynamics in determining regional vegetation responses to anthropogenic perturbations.
Keywords: biogeography; climate change; climate envelope; corvids; dispersal limitation; Garrulus; Holm oak; Iberian peninsular; incidence function; patch model; species migration; zoochory